The obligation of Constitutional Court to give a decision on opinion of Council Representatives in process of termination Indonesian President - Oktapani, Silm; Suhartono, Slamet; Hufron, Hufron; Mangesti, Yovita Arie (Technium Social Sciences Journal, 2023)
The 1945 Constitution as a constitution in post-reform Indonesia in 1998 underwent four amendments starting with the first amendment in 1999, the second amendment in 2000, the third amendment in 2001 and ending with the fourth amendment in 2002, by establishing 13 Articles and 3 Articles of Transitional Rules and 2 Articles of Additional Rules. Subhan Ali stated that changes to the constitution are a consequence of the life of a nation that aspires to create stronger and more certain constitutional conditions. Changes to the Constitution make this nation have a foundation to build a more progressive but also accountable country. Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, states: "Indonesia is a country based on law.